A comparison of individual force decline profiles during a fatiguing eccentric trunk flexion and extension protocol: a pilot study - Paksoy, Yasemin; Kpobi, David; Henschke, Jakob; Risch, Lucie; Engel, Tilman (Frontiers in Sports and Active Living, 2024)
Muscle fatigue, characterized by diminished force production and contraction sustainability, can impair muscle coordination and increase joint instability. Differing force profiles used in fatiguing tasks, such as prolonged eccentric trunk protocols, might provide insights into individualized strategies and resulting spinal stability. Thus, this study assessed individual differences in fatigue characteristics during an eccentric trunk flexion-extension protocol in a population of asymptomatic individuals. Methods: Twelve participants (2 f/10 m, 29 ±4 years, 78.4 ±16.9 kg, 1.76 ±0.10 m) performed an eccentric trunk flexion and extension protocol on an isokinetic dynamometer (45° flexion to 10° extension; 60°/s), with final analysis on 8 participants for trunk flexion and 11 for trunk extension due to data exclusions. Participants engaged in a maximal all-out (AO) task for 2 minutes. Each participant's torque output (Nm) was assessed on a repetition-by-repetition basis, and smoothened by a moving average of 5 repetitions. Individual time profiles for reaching fatigue thresholds (10%, 15%, 20% and 30% reduction of initial torque output), and inter subject variability (by coefficient of variation, CV in %) were assessed throughout the AO task. Further, percentage torque reduction and variability were assessed at mid (1-minute) and end (2-minute) of task. Results: On average, for flexor and extensor muscles combined, participants reached a force reduction of 10% within 23.2 ±19.1 s, of 15% within 44.9 ±19.6 s, of 20% in 62.4 ±26.3 s, and of 30% within 79.2 ±21.8 s. The variability between individuals for the timepoint of reaching the defined torque thresholds was assessed by CV ranged between 23.4% and 103.8% for trunk flexor muscles, and between 28.4% and 56.5% for trunk extensor muscles. Discussion: A reduction of up to 20% was seen on average for all participants within 1-minute of eccentric trunk flexion and extension. Different inter-individual force output profiles were seen throughout the AO protocol, potentially related to physiological, skill-based, technical, adaptational, and/or motivational factors. The increase in fatigue resulted in a reduction in variability among individuals. A 2-minute protocol effectively induced pronounced fatigue, offering insights into individual force profiles and strategies.